2018
DOI: 10.1590/1518-8345.2185.3006
|View full text |Cite
|
Sign up to set email alerts
|

Presenteeism and musculoskeletal symptoms among nursing professionals

Abstract: Objective: to identify the prevalence of musculoskeletal symptoms in two stages (before and after six months of the first stage) and its association with presenteeism among nursing professionals. Method: longitudinal study with quantitative data conducted in a Brazilian teaching hospital with 211 nursing professionals. The instruments used for data collection were: Cultural and Psychosocial Influences on Disability - CUPID Questionnaire, used to identify the musculoskeletal symptoms and the Stanford Presenteei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 23 publications
3
41
1
9
Order By: Relevance
“…This study investigated presenteeism due to WMSD and revealed a worrying situation due to the high prevalence observed in our and other studies. 10 , 11 , 21 This outcome considerably affects the worker, indicating an impossibility of performing work activities adequately. The negative impact on workers’ health and on their surroundings can become evident 5 when the causes of presenteeism are not removed or reduced, since injuries are then aggravated and the quality of work is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated presenteeism due to WMSD and revealed a worrying situation due to the high prevalence observed in our and other studies. 10 , 11 , 21 This outcome considerably affects the worker, indicating an impossibility of performing work activities adequately. The negative impact on workers’ health and on their surroundings can become evident 5 when the causes of presenteeism are not removed or reduced, since injuries are then aggravated and the quality of work is reduced.…”
Section: Discussionmentioning
confidence: 99%
“…10 Several studies reported the relationship between LBP among nurses and presenteeism. 11,12 However, these studies observed the relationship between overall LBP and work productivity. The factors and extent of LBP are various, and the treatment for LBP differs depending on the duration and the factors.…”
Section: Introductionmentioning
confidence: 93%
“…Several studies reported the relationship between LBP among nurses and presenteeism . However, these studies observed the relationship between overall LBP and work productivity.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies demonstrated that sleep disorders were reported by workers with Burnout (17) , even though there was an association between insomnia and musculoskeletal disorders -such as headaches, back and neck pain (18) -and that the number of nursing professionals who attend work complaining of some musculoskeletal symptom is considerable (19) . Some studies (14,(18)(19)(20) have indicated that the main body sites of musculoskeletal disorders are the regions of the head and cervical, lumbar and thoracic spine.…”
Section: Discussionmentioning
confidence: 99%